1962
DOI: 10.1084/jem.116.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity of Polypeptides (Poly Alpha Amino Acids)

Abstract: The antigenicity of synthetic polymers of a-amino acids has been studied in various species for different reasons. The original impetus to these investigations was the search for highly polymerized protein-like materials that could possibly be used as plasma volume expanders. Interest in these materials has increased since their anfigenicity offers a means of determining the minimum structural requirements for anfigenicity in protein-like materials. By the application of quantitative immunochemical studies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1963
1963
1973
1973

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Previously it was reported that 1/3 Hartley strain guinea pig sera (anti GLAT) cross reacted with the G60L40 polymer (11) and that of 5 human sera (anti GLAT) 3 gave cross reactions with G60L40 (13). As the data in Table VII shows, even sera which have a similar cross reaction with one polymer may differ as regards a second heterologous reaction.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previously it was reported that 1/3 Hartley strain guinea pig sera (anti GLAT) cross reacted with the G60L40 polymer (11) and that of 5 human sera (anti GLAT) 3 gave cross reactions with G60L40 (13). As the data in Table VII shows, even sera which have a similar cross reaction with one polymer may differ as regards a second heterologous reaction.…”
Section: Discussionmentioning
confidence: 75%
“…In previous reports on the immunogenicity in man (13) and guinea pigs (11) of a random straight chain polymer containing the aL amino acids glutamic acid36 lysine24 alanine35 and tyro sines** (GLAT) reference has been made to the immunogenicity in rabbits and mice. However data accumulated during the years dealing with extensive findings in rabbits and mice have not been reported.…”
mentioning
confidence: 99%
“…for immunizing rabbits and guinea pigs have been referred to in the previous publications (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…In contrast, random copolymers containing comparable amounts of 3 or 4 L-amino acids, such as glutamic acid, lysine, and alanine (GLA), 1 or glutamic acid, alanine, and tyrosine (GAT), or GLAT, have been found to be antigenic in rabbits. (2, 3), guinea pigs (4), and man (5), in nearly every subject tested. Random copolymers of 2 L-amino acids GA, GL, or LA, induce also an immune response in guinea pigs (4,6) but only in some animals and not in others.…”
mentioning
confidence: 99%